Tp–e interval and Tp–e/QT ratio in patients with Human Immunodeficiency Virus. Issue 1 (January 2018) - Ünal, Sefa; Yayla, Çağrı; Açar, Burak; Ertem, Ahmet G.; Akboğa, Mehmet K.; Gökaslan, Serkan; Erdöl, Mehmet A.; Sönmezer, Meliha Ç.; Kaya Kiliç, Esra; Ataman Hatipoğlu, Çiğdem; Tulek, Necla; Erdinç, Fatma S.; et al.
Abstract: Human Immunodeficiency Virus (HIV) infection and AIDS are known to cause cardiovascular diseases such as premature coronary artery disease, cardiomyopathy, and arrhythmias. Recently, Tp–e interval and Tp–e/QT ratio has been shown as a novel marker of ventricular repolarization. We aimed to evaluate the ventricular repolarization using Tp–e interval and Tp–e/QT ratio in patients with Human Immunodeficiency Virus (HIV) infection. Totally 48 patients with HIV and 60 control subjects were enrolled to the study. Tp–e interval, Tp–e/QT and Tp–e/QTc ratio were measured from the 12-lead electrocardiogram. Tp–e interval, Tp–e/QT ratio and Tp–e/QTc ratio were significantly higher in patients with HIV than control subjects (all p < 0.01). In correlation analysis, there were positive correlation between Tp–e interval and disease duration (r = 0.298, p = 0.048). and inverse correlation between Tp–e interval and CD4 count(r = −0.303, p = 0.036). Our study showed that Tp–e interval, Tp–e/QT and Tp–e/QTc ratios were increased in patients with HIV than control subjects.